Community policing - a critique of recent proposals - McCullagh, Ciaran (Economic & Social Studies, 1985)
In this article the proposals by the Association for Garda Sergeants and Inspectors, for a scheme of Community Policing, are outlined and discussed. Their innovatory nature is recognised but a number of problems - the notion of community which they use, difficulties in implementing such schemes and the question of whether they constitute a scheme of community policing - are considered. Finally the question is posed as to whether the Gardai could make the changes required to produce genuine community policing.
Keywords: Community policing; Crime - Ireland